Dynamic transcriptome unveils transcriptional network associated with chlorophyll degradation in tobacco leaves under high humidity and temperature - Su, Yike; Hu, Xiaodong; Yang, Xiaojuan; Su, Jiaen; Yang, Yanming; Chen, Yi; Jiang, Yonglei; Shi, Nan; Li, Mengxia; Zhang, Bo; Hu, Binbin (Frontiers in Plant Science, 2026)
IntroductionChlorophyll degradation is a key determinant of postharvest quality in flue-cured tobacco. Excessive nitrogen application increases chlorophyll accumulation, leading to green discoloration or mottling and reducing market value after curing.MethodsThis study investigated the effects of environmental humidity on chlorophyll degradation through gene ontology (GO) enrichment analysis, differentially expressed genes (DEGs) analysis, and correlation analysis.ResultsAt 93% relative humidity (RH), the rate of chlorophyll degradation was approximately twofold higher than that observed at 79% RH, particularly in nitrogen-imbalanced tobacco leaves. Transcriptome analysis of 63 samples revealed stage-specific expression patterns of chlorophyll catabolic genes (CCGs) under different curing conditions. PAO2 showed pronounced expression at 12 h, whereas CLH6 exhibited high expression at 18 h under high humidity. Under high-temperature stress during curing, SGR6 and CLH5 were strongly induced. Correlation-based transcriptional network analysis indicated that multiple transcription factor families, including ERF, NAC, MYB, and WRKY, were closely associated with CCG expression in response to humidity and temperature changes. Together, these findings suggest a complex transcriptional landscape linking environmental conditions with chlorophyll degradation during tobacco curing.DiscussionThe identified genes and transcriptional associations provide potential molecular candidates for future functional validation and the improvement of curing compatibility in tobacco.